Maslahah radical innovation: Breakthrough to achieve corporate sustainability in small and medium industries (SMI) batik in central java province - Sulistyawati, Dwi Retna; Mutamimah, Mutamimah; Hartono, Sri (Edelweiss Applied Science and Technology, 2024)
SMIs are an extraordinary industrial sector because they are able to absorb a larger sales force than large industries, and provide the most significant contribution to the national gross domestic product (GDP). Within the framework of national economic performance, the MSME sector has a large contribution to the Indonesian economy, which has more than 64.2 million business units, contributing 61.9% to Gross Domestic Product (GDP) and absorbing 97% of the workforce (Kemenparekraf, 2023). SMEs as drivers of the creative economy are able to produce the concept of collaboration between creativity, culture, economy, and technology in the contemporary world accompanied by the most dynamic innovation, and provide new opportunities for economic growth. This study aims to explore a new conceptual model that can fill the limitations of previous studies and research gaps that focus on the concept of radical innovation maslahah with risk handling mediation to achieve corporate sustainability. The concept of radical innovation maslahah is expected to improve risk handling and encourage the achievement of corporate sustainability in batik SMEs in Central Java province. The results of this study indicate that if radical halal innovation in products increases, it will trigger an increase in risk handling, supported by empirical data. Changes that occur as a result of radical innovation in products, have consequences for the existence of risks that require handling by batik SMEs. The conclusion of this study is that if radical humanist innovation in the process increases, it will trigger an increase in corporate sustainability, not supported by empirical data. This indicates that radical humanist innovation in the process is less able to encourage the achievement of corporate sustainability. If risk handling increases, it will trigger an increase in corporate sustainability, supported by empirical data. With increased risk handling in batik SMEs, it encourages the achievement of corporate sustainability.